A ética contemporânea no discurso da publicidade para a mulher - Nishida, Neusa Fumie (2007)
This research reflects on issues of contemporary ethics in advertising aimed at women. The discussion of such questions focuses on the deontological aspect (conviction). The aim of the study is to investigate how advertisements published in Claudia and Nova magazines articulate issues of such ethics. Thus, we sought to verify, through content analysis, whether the ads followed the principles contained in the Brazilian Code of Advertising Self-Regulation. In a second stage, it was intended to investigate, through discourse analysis, how the ads were built under the focus of ethics and women in today's society. It was concluded that the representations of deontological ethics in female advertising occur in a nonlinear and fragmented manner. Nonlinearity refers to the non-compliance with ethical principles by some ads analyzed. Fragmentation, on the other hand, concerns the way women are portrayed and how products are advertised in advertisements, based on different standards of conduct (principles) and based on diversified values. Now the ads present the products in a true way or not, sometimes women appear under a focus based on contemporary values ​​or traditional values ​​in a different way. (AU)